Surface Engineering Of Titanium Based Metal For Cell Interaction - Roshasnorlyza , Hazan (2014)

(untitled)
This research focused on the titanium surface modification with nanotopography morphology of TiO2 nanotubes. Cell-metal interaction between TiO2 nanotubes and PA6 bone marrow stromal cells were studied to understand the TiO2 nanotubes parameters that affect the cell growth. To achieve objective of this research work, titanium foil was transformed into different dimensionalities of TiO2 nanotubes via simple anodization method and characterized. Penyelidikan ini fokus kepada pengubahsuaian permukaan titanium dengan morfologi topografi tiub-nano TiO2. Tindak balas tiub-nano TiO2 dan sel stromal tulang PA6 dikaji bagi memahami pengaruh struktur tiub-nano terhadap pertumbuhan sel. Bagi menjayakan objektif penyelidikan ini, kerajang titanium telah diubahsuai kepada tiub-nano TiO2 yang mempunyai pelbagai dimensi melalui kaedah penganodan dan dicirikan.